BOR İÇERİKLİ ELEKTROTLARLA DÜŞÜK KARBONLU ÇELİK YÜZEYLERİNİN KAPLANMASI VE AŞINMA DİRENCİNİN İNCELENMESİ - KÖSELİ, BAHADIR (Fırat Üniveristesi, 2008)
Bu çalışmada, bor içerikli örtülü elektrotlar üretimiş ve düşük karbonlu çelik yüzeyleri tek paso halinde kaplanmıştır. Elektrot örtüsündeki bor içeriğinin kaplamanın mikroyapısı, sertliği ve aşınma direnci üzerindeki etkileri incelenmiştir. Kaplama işleminden sonra, WDX ve X-ray'i de içeren mikroyapı incelemeleri, sertlik ölçümleri ve abrasiv aşınma testleri sonuçlarından hareketle kaplamadaki bor içeriğinin birincil ve ötektik Fe2B oluşumunda ve dolayısıyla sertlik üzerinde etkili olduğu görülmüştür. Kaplamadaki bor miktarı arttığında mikroyapı ötektikten (Fe2B + ? -Fe), birincil F2B +ötektik +FeB yapıya doğru değişmiştir. Kaplamada kullanılan ısı girişinin de kaplama bor miktarı üzerinde kısmen etkili olduğu görülmüştür. Kaplamadaki bor miktarındaki artışla beraber aşınma direnci artmıştır. Mikroyapı inceleme, WDX ile X-ray analizleri ve mikrosetlik ölçüm sonuçlarından hareketle, yeni üretilen bor içerikli örtülü elektrotlar ile düşük karbonlu bir çelik yüzeyinde bor içeriğinin %7,2'ye kadar arttırılabileceği görülmüştür.

In the present study, the shielded metal arc welding electrodes containg boron were produced and low carbon steel plates were surfaced with single pass bead on plate welds. The effects of boron content in the shield of electrode on the microstructure, hardness and abrasive resistance of the surfaces were investigated. After surfacing, microstructural analysis including metallographic examination, wavelenght dispersive X-ray(WDX), X-ray, microhardness measuraments and abrasive wear tests were performed. From the results, it was seen that boron content in the coating was effective on the formation of primary and eutectic F2B, and consequently on the hardness. As the boron content in the coating increased the microstructure changed from eutectic structure (Fe2B + ? -Fe) to primary Fe2B with eutectic + FeB structure the heat input was also relatively effective on the amount of boron content of the coating. Abrasihve wear resistance of the coating increased with the increase in boron content. As a result, from the microstructural observations, WDX and X-ray analysis and microhardness measuraments, it was concluded that boron content of a low carbon steel surface can be increased up to 7,2 wt % by newly developed boron containing shielded metal arc welding electrodes.
The coating of low carbon steel surface with the electrodes containg boron and investigation of abrasive wear behaviour
Keywords: Metalurji Mühendisliği